High sustained virological response rates using imported generic direct acting antiviral treatment for hepatitis C - Andrew Hill; Giten Khwairakpam; James Wang; Sergey Golovin; Julia Dragunova; Rachel Smith; Vicky Houghton-Price; Roxanna Korologou-Linden; Sanjay Nath; Anna Savage; Greg Jefferys (Elsevier, 2017)
Background: High prices of direct acting antivirals (DAAs) for hepatitis C virus (HCV) can lead to restrictions on access to treatment in high- and middle-income countries. An increasing number of people in these countries are treating their HCV infection with generic drugs produced in India, China, Bangladesh or Egypt. This analysis assessed the efficacy of generic imported DAAs. Methods: Patients sourced generic versions of sofosbuvir (SOF), ledipasvir (LDV) and daclatasvir (DCV) from suppliers in India, Bangladesh, China and Egypt via three buyers' clubs. The choice of DAAs and the length of treatment were determined on baseline RNA levels, HCV genotype and stage of fibrosis. Patient HCV RNA levels were evaluated pre-treatment, during treatment, at end of treatment (EOT) and then for sustained virological response (SVR) at 4, 12, and 24 weeks, normally by a treating clinician. Results: Overall 616 patients submitted results: 199 from an Australian buyers' club, 205 from a South-east Asian buyers' clubs, and 212 from an Eastern European buyers' club. Of the 616 patients treated, 276 received SOF/LDV (35 with ribavirin [RBV]) and 340 received SOF/DCV (61 with RBV). At baseline, 61% were male, 52% had HCV genotype 1 and 11% had liver cirrhosis. The mean age was 44.3 years and the mean baseline HCV RNA was 6.9 log10 IU/mL. A rapid virological response (RVR) was observed in 314/375 (84%) of the patients treated. Based on currently available data, the percentage of patients with HCV RNA below the lower limit of quantification (LLoQ) was 99% (234/237) at EOT, 99% (299/303) at SVR4 and 99% (247/250) at SVR12. Conclusions: In this analysis, treatment with imported generic DAAs achieved high rates of HCV RNA undetectability at the end of treatment, and SVR12 in 99% of patients evaluated to date. Mass treatment with generic DAAs is a feasible and economical alternative route of accessing curative DAAs, where the high prices for branded alternatives prevent access to treatment.